Pengaruh Kepemimpinan Etis terhadap Keterlibatan Karyawan dan Keberlanjutan Organisasi dalam Profesi Akuntansi terhadap Perusahasaan Aktif Indonesia - Kazteny Indrawan, Karyeen (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This study analyzes the influence of ethical leadership on the level of employee engagement and organizational sustainability in the accounting profession in Indonesia. Through quantitative research methods using Likert scale questionnaires 1-5, 20 employee respondents from active companies in Indonesia were taken as samples using random sampling techniques. The questionnaire was designed to measure variables of ethical leadership, employee engagement, and organizational sustainability. The collected data were analyzed using classical assumption test and multiple linear regression analysis with SPSS version 26. Regression test results showed a significant positive relationship between ethical leadership and employee engagement and organizational sustainability. A positive B1 value (0.203) indicates that a one-unit increase in ethical leadership contributes to a 0.203-unit increase in employee engagement and organizational sustainability. These findings illustrate that investing in value-based ethical leadership can have a positive impact on employee engagement and organizational sustainability within the corporate environment in Indonesia.